Inhibitive Effects of Recent Exceeding Air Temperature Optima of Vegetation Productivity and Increasing Water Limitation on Photosynthesis Reversed Global Greening. Issue 11 (21st November 2022) - Chen, Baozhang; Ke, Yu; Ciais, Philippe; Zeng, Zhenzhong; Black, Andy; Lv, Honggang; Huang, Mengtian; Yuan, Wenping; Xiao, Xiangming; Fang, Junjun; Hou, Kun; Wang, Ying‐Ping; et al.
Abstract: Global terrestrial vegetation dynamics have been rapidly altered by climate change. A widespread vegetation greenness over a large part of the planet from the 1980s to early this century has been reported, whereas weakening of CO2 fertilization effects and increasing climate extremes and the adverse impact of increasing rate of warming and severity of drought on vegetation growth were also reported. Earth system models project that the land carbon sink will decrease in size in response to an increase in warming during this century. How global vegetation is changing during this century in response to global warming and water availability across spatial and temporal scales remains uncertain. Our understanding of the widespread vegetation greening or browning processes and identifying the biogeochemical mechanisms remain incomplete. Here we use multiple long‐term satellite leaf area index (LAI) records to investigate vegetation growth trends from 1982 to 2018. We find that the widespread increase of growing‐season integrated LAI (greening) since 1980s was reversed ( p ‐value < 0.05) around the year 2000 over 90% of the global vegetated area, and continued in only 10% of the global vegetated area. The reversal of greening trend was largely explained by the inhibitive effects of excessive optimal temperature on photosynthesis in most of the tropics and low latitudes, and by increasing water limitation (increasing in atmospheric vapor pressure deficit and decreasing in soil water availability) in the northern high latitudes (>45°N). Overall, the reversal of greening trend since 2000 weakened the negative feedback of carbon sequestration on the climatic system and should be considered in the strategies for climate warming mitigation and adaptation. Our findings of the diversity of processes that drive browning across bioclimatic‐zones and ecosystems and of how those driving processes are changing would enhance our ability to project global future vegetation change and its climatic and abiotic consequences. Plain Language Summary: A widespread vegetation greenness over a large part of the planet from the 1980s to early this century has been reported, whereas weakening of CO2 fertilization effects and increasing climate extremes and the adverse impact of increasing rate of warming and severity of drought on vegetation growth were also reported. We find that the widespread increase of growing‐season integrated LAI (greening) since 1980s was reversed ( p ‐value < 0.05) around year 2000 over 90% of the global vegetated area, and continued in only 10% of the global vegetated area. The reversal of greening trend was largely explained by the negative influence of excessive air temperature on photosynthesis of vegetation growth in most of the tropics and low latitudes, and by increasing in atmospheric vapor pressure deficit and decreasing in soil water availability in the northern high latitudes (>45°N). Our findings of the diversity of browning mechanisms across bioclimatic‐zones and ecosystems are useful for projecting global future vegetation change and its climatic and abiotic consequences. Key Points: The widespread increase of vegetation greening trend since 1980s was reversed around the year 2000 over 90% of the global vegetated area The leveling off of global greenness arisen from recent exceeding optimal temperature and increasing water limitation for photosynthesis Our findings of the diversity of browning mechanisms are useful for projecting global future vegetation change and its climatic consequences